PENGARUH LINGKUNGAN KELUARGA TERHADAP MOTIVASI BERWIRAUSAHA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNTAN - Paramitha, Een; Aminuyati, Aminuyati; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the effect of family environment on student entrepreneurship motivation in the Economics Education Study Program, FKIP UNTAN. The researcher applied quantitative descriptive method for this study. The sample in this research were students of the Economic Education Study Program obtained through Random Sampling. The researcher used questionnaire to determine the effect of family environment to the entrepreneurship motivation, with the formulation; Y = 77.682 + 0.532X. Based on the calculation using SPSS 18.0, t-count was 3,843, while t-table with 56 respondents had the degree of freedom df = n - k or 56 - 2 = 54, so the t-table was 2,004, from the result, it was compared between the results of t-count and t-table . It was concluded that t-count > t-table (3,843> 1,673), therefore Ha was accepted and Ho was rejected. The determination coefficient in the results of the study showed the effect contribution between the independent variable and the dependent variable with the amount of 0.215 or 21.5%. The rest were influenced by other factors. It can be inferred that there were found the influence of the Family Environment on the Students? Entrepreneurship Motivation in Economic Education Study Program of FKIP UNTAN.Keywords: Family Environment, Entrepreneurship Motivation